(untitled) (Proceedings of International Educators Conference, 2024)
Currently, the country is reforming the accounting and financial reporting system in the Republic of Uzbekistan. The article presents a study of current accounting in agricultural products, grain crops, and reporting of biological assets, which cannot be compared with international standards. The authors studied accounting with the implementation of international financial reporting standards (IFRS).Thus, the convergence of accounting to international standards is an important step in the development of accounting in the Republic of Uzbekistan. The study revealed the preparation of accounting reports, which reflect separately the valuation of biological assets, for example, crop production, and separately the cost of the harvested crop. Also, an assessment and accounting of finished grain production products at fair value is proposed, which will allow assessing the real productivity of production and the effectiveness of completed transactions.